2003
DOI: 10.1091/mbc.e02-10-0676
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegansUNC-98, a C2H2 Zn Finger Protein, Is a Novel Partner of UNC-97/PINCH in Muscle Adhesion Complexes

Abstract: To further understand the assembly and maintenance of the muscle contractile apparatus, we have identified a new protein, UNC-98, in the muscle of Caenorhabditis elegans. unc-98 mutants display reduced motility and a characteristic defect in muscle structure. We show that the major defect in the mutant muscle is in the M-lines and dense bodies (Z-line analogs). Both functionally and compositionally, nematode M-lines and dense bodies are analogous to focal adhesions of nonmuscle cells. UNC-98 is a novel 310-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(101 citation statements)
references
References 54 publications
6
94
1
Order By: Relevance
“…Consistent with this perspective, a recently published crystal structure of LIM1 of PINCH bound to the ANKR domain of ILK confirms that human PINCH Q40 is a key residue in maintaining the PINCH-ILK interaction, and highlights that LIM1 of PINCH undergoes a conformational 'twist' upon binding to ILK that could create docking sites for additional partners (Chiswell et al, 2008;Yang et al, 2009). Several studies have identified novel binding partners for LIM1 of PINCH in C. elegans and in human cultured podocytes (Mercer et al, 2003;Qadota et al, 2007;Wang et al, 2011). However, additional research is required to assess the conservation of these PINCH-LIM1 binding partners in other organisms, as well as any potential roles they may have in PINCH localization and integrin effector function.…”
Section: Requirements For Pinch and Ilk Localization At Muscle Attachmentioning
confidence: 99%
“…Consistent with this perspective, a recently published crystal structure of LIM1 of PINCH bound to the ANKR domain of ILK confirms that human PINCH Q40 is a key residue in maintaining the PINCH-ILK interaction, and highlights that LIM1 of PINCH undergoes a conformational 'twist' upon binding to ILK that could create docking sites for additional partners (Chiswell et al, 2008;Yang et al, 2009). Several studies have identified novel binding partners for LIM1 of PINCH in C. elegans and in human cultured podocytes (Mercer et al, 2003;Qadota et al, 2007;Wang et al, 2011). However, additional research is required to assess the conservation of these PINCH-LIM1 binding partners in other organisms, as well as any potential roles they may have in PINCH localization and integrin effector function.…”
Section: Requirements For Pinch and Ilk Localization At Muscle Attachmentioning
confidence: 99%
“…Similarly, UNC-97 binds PAT-4 in yeast two-hybrid assays and is recruited to dense bodies and M-lines by PAT-4 (Hobert et al, 1999). UNC-97 also interacts with UNC-98, a C2H2 Zn-finger protein that localizes to M-lines (and possibly dense bodies) and to the nucleus (Mercer et al, 2003). UNC-98 might be involved in maintaining muscle structure, although the underlying mechanisms are not understood.…”
Section: Maintaining Integrity Of Dense Bodies and M-linesmentioning
confidence: 99%
“…The significance of the nuclear UNC-82::GFP signal ( Figure 3D) is not known, but is seen with both wild-type UNC-82::GFP and E424K::GFP. Interestingly, nuclear localization has also been reported for the zinc-finger-containing M-line protein UNC-98/ZnF (Mercer et al 2003). The mammalian UNC-82 orthologs exhibit nuclear localization under conditions of stress (Kuga et al 2008;Hou et al 2011).…”
Section: Mutant Unc-82 E424k Colocalizes With Abnormal Paramyosin Accmentioning
confidence: 81%
“…Mouse monoclonal antibodies 5/6 (1:500 dilution), 5/8 (1:500 dilution), 5/23 (1:200 dilution), and rabbit polyclonal antibody EU131 (1:200) were used for immunofluorescence localization of myosin A, myosin B, paramyosin, and UNC-98, respectively (Miller et al1983;Mercer et al 2003). Rabbit and mouse anti-GFP antibodies from Jackson ImmunoResearch Laboratories (West Grove, PA) were used at 1:250 dilution.…”
Section: Microscopymentioning
confidence: 99%